Regime and periphery in Northern Yemen : the Huthi phenomenon - Salmoni, Barak A. (Rand Corporation monograph series, 2010)
For nearly six years, the Government of Yemen (GoY) has conducted military operations against groups of its citizens north of San'a, known as "Huthis" or Believing Youth (BY). In spite of using all coercive and ideological means at its disposal, the GoY has been unable to fully subdue the Huthi movement, which has sustained a material and popular base over successive phases of armed conflict into the winter of 2010. At the same time, the regime has confronted mounting southern discontent and al-Qa'ida-inspired terrorism, as well as severely contracting economic prospects. The war against the Huthis, however, has of late absorbed more of the GoY's political attention and coercive resources than these other issues, weakening the state's ability to deal with the multiple challenges it faces. The Huthi conflict thus presents an enduing threat both to the regime of President 'Ali 'Abdullah Saleh and to the stability of Yemen as a unitary state. It also fundamentally impairs the GoY's ability to function as a U.S. partner for regional security, stability, and counterterrorism. Furthermore, armed confrontation between the Kingdom of Saudi Arabia and Huthi fighters beginning in November-December 2009 has added a transnational dimension to the conflict and risks pulling in other regional countries, such as Iran. Such an eventuality would fundamentally undermine security in the Arabian Peninsula and Gulf, harming the regional interests of the United States while it is engaged in Iraq, Afghanistan, and nuclear negotiations with Iran